PSYCHOLOGICAL RESILIENCE OF HEALTHCARE WORKERS FACING DISASTERS: A SCOOPING REVIEW - Elia Oktaviana; Alya Gustiyana Herman; Retti Rismayati; Tahta Aditya Andi F. Hurudji; Ririn Zuhairini (Journal of Indonesian Anesthesiology Nursing, 2025)
Background: Psychological resilience is an adaptive ability that enables healthcare workers to maintain emotional and mental stability when facing stressful conditions caused by disasters. This review aims to map and synthesize the current evidence on psychological resilience among healthcare workers during disaster situations. Methods: This scooping review followed the Arksey and O’Malley framework and PRISMA 2009 guidelines. Literature searches were conducted in Science Direct, PubMed, and Google Scholar for articles published between 2015–2025. Ten articles met the inclusion criteria, consisting of seven quantitative studies, two review studies, and one qualitative concept analysis. Results: Internal factors influencing resilience included self-efficacy, emotional regulation, adaptive coping, and intrinsic motivation. External factors involved social support, supportive leadership, and organizational preparedness. Several psychological interventions such as mindfulness training, emotional regulation programs, and integrated disaster nursing training were shown to significantly increase resilience and reduce stress among healthcare workers. Conclusion: Psychological resilience plays a crucial role in maintaining mental well-being and performance during disaster response. Strengthening resilience through structured psychological interventions and supportive workplace environments should be integrated into disaster preparedness strategies to optimize healthcare workers’ readiness and mental stability during crises. Keywords: psychological resilience; healthcare workers; disaster; mental well-being; scooping review